Identification of clinical factors related to antibody‐mediated immune response to the subfornical organ. (22nd April 2022) - Nakamura‐Utsunomiya, Akari; Goda, Satoshi; Hayakawa, Seiichi; Sonoko, Sakata; Hoorn, Ewout J.; Blanchard, Anne; Saito‐Hakoda, Akiko; Kakimoto, Haruna; Hachiya, Rumi; Kamimura, Miki; Kawakita, Rie; Higuchi, Shinji; et al.
Abstract: Objective: We recently reported cases of adipsic hypernatremia caused by autoantibodies against the subfornical organ in patients with hypothalamic‐pituitary lesions. This study aimed to clarify the clinical features of newly identified patients with adipsic hypernatremia whose sera displayed immunoreactivity to the mouse subfornical organ. Design: Observational cohort study of patients diagnosed with adipsic hypernatremia in Japan, United States, and Europe. Methods: The study included 22 patients with adipsic hypernatremia but without overt structural changes in the hypothalamic‐pituitary region and congenital disease. Antibody response to the mouse subfornical organ was determined using immunohistochemistry. The clinical characteristics were compared between the patients with positive and negative antibody responses. Results: Antibody response to the mouse subfornical organ was detected in the sera of 16 patients (72.7%, female/male ratio, 1:1, 12 pediatric and 4 adult patients). The prolactin levels at the time of diagnosis were significantly higher in patients with positive subfornical organ (SFO) immunoreactivity than in those with negative SFO immunoreactivity (58.9 ± 33.5 vs. 22.9 ± 13.9 ng/ml, p < .05). Hypothalamic disorders were found in 37.5% of the patients with positive SFO immunoreactivity. Moreover, six patients were diagnosed with rapid‐onset obesity with hypothalamic dysfunction, hypoventilation, and autonomic dysregulation/neural tumor syndrome after the diagnosis of adipsic hypernatremia. Plasma renin activity levels were significantly higher in patients with serum immunoreactivity to the Nax channel. Conclusions: The patients with serum immunoreactivity to the SFO had higher prolactin levels and hypothalamic disorders compared to those without the immunoreactivity. The clinical characteristics of patients with serum immunoreactivity to the subfornical organ included higher prolactin levels and hypothalamic disorders, which were frequently associated with central hypothyroidism and the presence of retroperitoneal tumors.